Pharmacokinetics of sulbactam in humans. - Foulds, G (1983)
Sulbactam, a new beta-lactamase inhibitor, has pharmacokinetic characteristics in humans similar to those of ampicillin and amoxicillin. Its half-life in humans is approximately 1 h. In a two-compartment pharmacokinetic model, the apparent volume of distribution for the central compartment is approximately 12 liters, and half of the dose is found in the central compartment in the postdistributive phase. Approximately 75% of a parenteral dose is excreted unchanged in urine. The coadministration of sulbactam with ampicillin, penicillin G, or cefoperazone has essentially no effect upon the kinetics of either the beta-lactam antibiotic or sulbactam.